2012
DOI: 10.1111/j.1742-7843.2012.00920.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Drug Utilization in Greece Sex dependent? A Population‐based Study

Abstract: Despite scarce data pertaining to prescription drug sales in Greece, the lack of large-scale epidemiological studies has made it difficult to elaborate on putative differences regarding drug consumption patterns between the two sexes. Herein, we sought to investigate whether sex may have an impact on medication trends of the Greek population. The data reported are part of a survey conducted under the auspices of the National Center for Social Research. Information was collected from 2499 Athenian citizens. Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
14
2
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 75 publications
7
14
2
6
Order By: Relevance
“…The finding that self-medication is most practiced by female individuals has also been found in other publications 2 , 4 , 9 , despite national and 11 international 3 , 8 , 14 , 22 , 26 studies indicating that self-medication is more prevalent among men. The results of this study may have influenced by the fact that women suffer more with headaches, muscle pain and chronic pain conditions, such as migraine, and use painkillers and muscle relaxers from an early age for pain relief during menstruation or dysmenorrhoea 2 , 19 .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The finding that self-medication is most practiced by female individuals has also been found in other publications 2 , 4 , 9 , despite national and 11 international 3 , 8 , 14 , 22 , 26 studies indicating that self-medication is more prevalent among men. The results of this study may have influenced by the fact that women suffer more with headaches, muscle pain and chronic pain conditions, such as migraine, and use painkillers and muscle relaxers from an early age for pain relief during menstruation or dysmenorrhoea 2 , 19 .…”
Section: Discussionsupporting
confidence: 73%
“…Self-medication is a worldwide phenomenon, the prevalence of such can differ depending on the population studied, the method and the recall period employed: in Germany 9 , the prevalence for medication use on a self-medication basis was 27.7%; in Portugal 14 , this was 26.2%; in Spain 7 , 12.7%; in Cuba 8 , 7.3%; in Athens-Greece 2 , 23.4%; in the Catalonia region of Spain 20 , 34.0% among men and 25.0% among women; and in Pondicherry-India 22 , this was equal to 11.9%.…”
Section: Introductionmentioning
confidence: 95%
“…This finding confirms a number of recent studies that showed a higher use of AD in women compared to men. (Athanasopoulos et al, 2013; Atlantis et al, 2012; Kuo et al, 2011; Lockhart and Guthrie, 2011; Meng et al, 2013; Mojtabai and Olfson, 2014; Parabiaghi et al, 2011; Sundell et al, 2011; Wu et al, 2012) We also observed that the prevalence of AD prescriptions reached a peak at age 50–64 years in women but not in men. This age group corresponds approximately with the early-postmenopausal years (the median age at menopause in the United States is 51 years).…”
Section: Discussionsupporting
confidence: 65%
“…This finding corroborates those from other studies, showing that girls use medicines in higher proportions than boys and that female gender is a strong correlate of prescription analgesic abuse and dependence Simoni-Wastila et al, 2008;Stoelben, Krappweis, Rossler, & Kirch, 2000). In Greece, gender differences have also been noted in samples of the general population (Athanasopoulos, Pitychoutis, Messari, Lionis, & Papadopoulou-Daifoti, 2012;Kokkevi, Fotiou, & Richardson, 2007;Pappa et al, 2011), while in another study female gender predicted misuse of tranquilisers/ sedatives among Greek adolescent students (Kokkevi et al, 2008). The emergence of female gender as a correlate of misuse of prescription analgesics in the present study coupled with the fact that girls in Greece report drug use in significantly lower proportions than boys (Hibell et al, 2012) suggests that prescription analgesic misuse is more likely to be associated with self-treating than recreational motives.…”
Section: Discussionsupporting
confidence: 91%